Isolation of chlamydia in irradiated and non-irradiated McCoy cells. Issue 12 (December 1975) - Johnson, L; Harper, I A
Abstract : Specimens from eye and genital tract were cultured in parallel in irradiated and non-irradiated McCoy cells and the frequency of isolation of chlamydia using these culture methods was compared. There was a significant difference between the frequencies of isolation; irradiated McCoy cells produced a greater number of positive results.